CRITICAL AND CREATIVE THINKING SKILLS TO SOLVING MATH STORY PROBLEMS IN ELEMENTARY SCHOOL STUDENTS - Sunnah Ida; Rahmat Aziz; Wahyu Hengki Irawan (Universitas Islam Negeri (UIN) Mataram, 2021)
Following the 2013 curriculum, the mathematics learning process requires critical and creative skills that can help students solve a problem on math problems. Students who maximize critical thinking can conclude the information obtained, know how to use the information in math story problems, and find sources of supporting communication in solving a problem. In addition, students must have creative thinking skills that find new ideas or ideas from math story problems. This study discussess the importance of critical and creative thinking skills in elementary school students in solving math story problems. The method used in this research is the library research method with a qualitative approach. Critical thinking skills are an active process that continuously and thoroughly contains the contents of one's thoughts about something in-depth to decide what to believe or do. At the same time, creative thinking skills are the process of bringing up or bringing up a new idea based on a combination of previous experience. New ideas emerge from old ideas combined in new ways. The learning model that supports students in solving story problems is Problem Solving.